1985
DOI: 10.1177/004728758502300403
|View full text |Cite
|
Sign up to set email alerts
|

A Demand Function For Length of Stay: The Evidence From Virginia Beach

Abstract: This article estimates the effects of cost and other factors on length of stay inVirginia Beach, Virginia, and analyzes the impact on tourism of decisions concerning advertising, the tax structure, and a proposed capital improvements project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1
5

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 3 publications
3
42
1
5
Order By: Relevance
“…In addition to the cost of accommodation, type of accommodation itself can have an effect on the length of stay. Past studies identified the effect of accommodation costs on temporal choice (Alegre & Pou, 2006;Ferrer-Rosell, Martínez-Garcia, & Coenders, 2014;Martínez-Garcia & Raya, 2008;Salmasi, Celidoni, & Precidano, 2012;Silberman, 1985).…”
Section: Control Variable: Accommodation Typesmentioning
confidence: 99%
“…In addition to the cost of accommodation, type of accommodation itself can have an effect on the length of stay. Past studies identified the effect of accommodation costs on temporal choice (Alegre & Pou, 2006;Ferrer-Rosell, Martínez-Garcia, & Coenders, 2014;Martínez-Garcia & Raya, 2008;Salmasi, Celidoni, & Precidano, 2012;Silberman, 1985).…”
Section: Control Variable: Accommodation Typesmentioning
confidence: 99%
“…The explanatory variables (X ð1Þ it and X ð2Þ t ) of tourist expenses are described as follows: Duration of stay (X ð1Þ it ). If we consider that the number of days that a tourist spends away from the usual place of residence is ''vacation quantity'' (Silberman, 1985), we can assume a positive relationship between the duration of stay and expenditure incurred during the holiday: a greater number of days implies greater expenditure. Literature shows that the number of days spent at a certain destination (along with the number of tourists) has an influence on the level of income from tourist activity (Alegre & Pou, 2003).…”
Section: Article In Pressmentioning
confidence: 99%
“…A maior parte dos estudos estima que o tempo de permanência no destino é um bem normal, isto é, maiores níveis de renda levam a permanências mais longas (Barros et al, 2008;Gokovali et al, 2007;Mak et al, 1977;Peypoch et al, 2012;Silberman, 1985;Walsh & Davitt, 1983). No entanto, Hellström (2006) e não encontraram evidências de qualquer relação entre renda e permanência.…”
Section: Fundamentação Teóricaunclassified
“…Quanto maior a renda familiar, menor é a permanência esperada do turista no país. Essa relação é relativamente incomum, sendo conflitante com as evidências empíricas proporcionadas pela maior parte dos estudos anteriores (Barros et al, 2008;Gokovali et al, 2007;Mak et al, 1977;Peypoch et al, 2012;Silberman, 1985;Walsh & Davitt, 1983). No entanto, a inferioridade é consistente com as evidências encontradas por Blaine et al (1993) e Mak e Nishimura (1979).…”
Section: Discussão E Considerações Finaisunclassified